Compliance with EU Law from 1989 to 2018: The Commission's Shift from a Normative to a Regulative Approach. (11th September 2022) - Pircher, Brigitte
Abstract: This study analyses the European Commission's strategies to counteract Member States' non‐compliance with EU law between 1989 and 2018. Based on a theoretical framework that distinguishes between a normative and a regulative approach in the Commission's strategies, the study conducts a semi‐automatic content analysis of all annual reports on monitoring the application of EU law and further supports this analysis with other EU sources. The results demonstrate that the Commission shifted from a normative approach based on management tools in the late 1980s and early 1990s to a more regulative approach with enhanced enforcement four decades later. Moreover, the Commission's role as driver for European integration has changed. In times of crisis and increased domestic contestation, the Commission has become a more authoritarian prosecutor of European policies.